Assessment of Vitamin D Level in Sera of Primary School Students in Babylon Province (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The spread of insufficiency of vitamin D may expose primary students at hazard for bone development, innate and adaptive immune responses, and increases risk of certain chronic diseases. The study provides an examination of the pervasiveness of 3 levels of sera 25(OH)D (≥30, 29-20, and